GIS and environmental monitoring : applications in the marine, atmospheric and geomagnetic fields - Kolios, Stavros; Vorobev, Andrei V.; Vorobeva, Gulnara R.; Stylios, Chrysostomos (Springer, 2017)
This book constitutes a notable contribution to investigate and present the capabilities of Geographic Information Systems (GIS) and their applicability and usefulness in environmental-related applications and sciences. The focus is on the design, creation, development and operation of integrated Web-based GIS applications for weather, marine and atmospheric environments, and Earth's magnetic field. More specifically, the aim of this book is to present characteristic applications of GIS to environmental monitoring including GIS solutions for eco-mapping sea and port-related parameters, climate changes, and geomagnetic field. In the first part of the book, the description of every application includes the user requirements, the design and development stages performed and the presentation of the final outcome, its capabilities and services. The Web-based applications are developed through different innovative approaches, such as cloud GIS and Google Apps for GIS, justifying the merit of WebGIS in the world of the environmental applications. The second part of the book provides an overview of geomagnetic field parameters and reveals the potential of using GIS for modeling and analyzing of the Earth's magnetic (geomagnetic) field and its parameters. Here, the authors present the recently introduced phenomenon called "geomagnetic pseudostorm", which is modeled and further analyzed here with GIS technology and tools. This book appeals to those interested in various areas where spatial information becomes of paramount relevance (e.g. social and economic research and mapping, environmental and climate research, decision support systems, public services, and especially for geomagnetic field variations and for the design of warning systems for natural disasters). It presents modern methods and approaches to visualize and analyze spatial information using innovative techniques, procedures, and tools of WebGIS technology. In this book, the readers find a valuable companion in their efforts to design and develop their own WebGIS applications, as it includes useful examples of developing (Web)GIS applications regarding the monitoring of marine and atmospheric environments, as well as applications that deal with meteorological issues and the Earth's magnetic field along with solar activity (space weather information). This book can also serve as a useful reference source for graduates, researchers and professionals related to the areas indicated above.
Keywords: Geographic information systems.; Environmental monitoring -- Remote sensing.; elektronické knihy; electronic books